Peningkatan Ketrampilan UKM Logam Melalui Pelatihan Pembuatan Mesin Perajang Bawang Merah Di Kota Nganjuk - Santoso, Eko Budi; ., Saat Riyanto; Herraprastanti, Eva Hertnacahyani; ., Ichlas Imran; ., Windarti . (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2020)
Nganjuk is one of the agrarian cities in East Java that has great potential in producing shallots. Shallots sold are in the form of leafy or leafless onions which are usually called "protholan". During the harvest season, the amount of onion is very large which causes a decrease in the selling price of shallots. This resulted in the onion farmers only get a small profit. Besides agriculture, in the city of Nganjuk also began to grow a business in the field of small industries namely welding. To synergize the two potentials, an activity is needed. in the form of training for making onion chopper tools for Metal SMEs, especially welding. The tool is made using the system "Chopper with simple cutter". In this activity includes the theory of introduction of metal materials, food grade material, how to read technical drawings, machining and assembly, and the practice of making chopper tools. The conclusion of this activity is the increased knowledge and experience for Metal SMEs, and will also be a new product that is very suitable to be marketed in the Nganjuk area as a producer of shallots. And for farmers, it will be one solution to solve the problem of the selling price of shallots to make new products in the form of sliced shallots. And in general, it will increase income for Metal SMEs and shallots farmers.